Moral judgments and validity of law - A. B. Didikin (Омский научный вестник: Серия "Общество. История. Современность")
The paper is devoted to the analysis of A. V. Nekhaev’s arguments, which substantiate the primary moral basis of legal regulations. On the basis of modern discussions in the legal philosophy, the groundlessness of arbitrary transfer of moral judgments in the field of law is proved, as well as on the example of judicial practice, it is demonstrated that the judicial process does not include a moral interpretation of actions, by virtue of which the nature of the sanction or punishment can be determined. As additional arguments for the definition of the legal force theory, the arguments of the normativism adapted to the modern realities of lawmaking are given